2022
DOI: 10.3389/fnmol.2021.797253
|View full text |Cite
|
Sign up to set email alerts
|

Roles of N-Methyl-D-Aspartate Receptors (NMDARs) in Epilepsy

Abstract: Epilepsy is one of the most common neurological disorders characterized by recurrent seizures. The mechanism of epilepsy remains unclear and previous studies suggest that N-methyl-D-aspartate receptors (NMDARs) play an important role in abnormal discharges, nerve conduction, neuron injury and inflammation, thereby they may participate in epileptogenesis. NMDARs belong to a family of ionotropic glutamate receptors that play essential roles in excitatory neurotransmission and synaptic plasticity in the mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 252 publications
0
9
0
Order By: Relevance
“…Numerous studies have revealed that glutamate is involved in the mechanism and treatment of epilepsy. For example, abnormalities in glutamatergic function have been observed in animal models of epilepsy, 5 and biochemical analysis in human epileptic brain tissue revealed an increase in glutamate levels. 6,7 In addition, glutamate agonists induce seizures while glutamate antagonists inhibit seizures, 8 and several antiepileptic drugs (AEDs) decrease synaptic glutamate.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that glutamate is involved in the mechanism and treatment of epilepsy. For example, abnormalities in glutamatergic function have been observed in animal models of epilepsy, 5 and biochemical analysis in human epileptic brain tissue revealed an increase in glutamate levels. 6,7 In addition, glutamate agonists induce seizures while glutamate antagonists inhibit seizures, 8 and several antiepileptic drugs (AEDs) decrease synaptic glutamate.…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance in the regulatory mechanisms of neuronal excitation and inhibition leads to excessive synchronous firing of neurons. In this process, glutamate and other neurotransmitters are widely involved in the regulation process between neuronal excitation and inhibition by activating corresponding receptors (4). The occurrence of PTE is related to excessive release of glutamate.…”
mentioning
confidence: 99%
“…36 Accordingly, altered glycine metabolism is implicated in various neurodevelopmental defects. [37][38][39][40] Furthermore, increased levels of glycine and serine were detected in the plasma samples of individuals with Rett syndrome (RTT; MIM #312750), a condition including epilepsy, microcephaly and DD/ID among cardinal clinical features. 41 GLDC, encoding the glycine decarboxylase, one of the four proteins forming the mitochondrial glycine cleavage system (GCS), and GAMT, encoding the guanidinoacetate Nmethyltransferase, were among the top downregulated genes in the RNA-seq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is well known that NMDARs belong to a family of ionotropic glutamate receptors that play essential roles in excitatory neurotransmission and synaptic plasticity in the mammalian CNS. 40 Furthermore, several studies suggest that NMDARs contribute to the genesis and spread of the abnormal paroxysmal discharges, neuron injury and in ammation, and thus may participate in epileptogenesis. 40 Furthermore, glycine level affects L-serine one and the latter amino acid is the precursor of D-serine [42][43] : the observed increase in proband's LCL D-serine level could further induce NMDA receptor hyperactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation